A tecnologia da informação e comunicação dentro do ambiente escolar e sua utilização no processo de ensino aprendizagem - MACHADO, Thiago Rodrigues (2019)
The present work aims to discuss the use of information and communication technologies in the school environment and its use in the process of teaching learning. Since in recent years there have been several changes in society and technological advances have played a fundamental role, so through this work we will seek to reflect on the application of these technological resources within schools since there is the possibility of these tools to help both teachers and other participants in the educational system. The text will also address some public policies that have focused on expanding the use of technological resources both within and outside of schools. To help us better understand how this relationship between education and technology occurs, we conducted a survey at a Municipal School in the city of Abaetetuba-PA and through the questionnaire it was possible to understand how to use the ICT in the development of pedagogical work. In the sequence, through the results of this research we can see that elaborating an educational project in which the technologies allied to the pedagogical activities can boost the educational process and the information and communication technologies help both the teachers and the students to expand their possibilities of teaching and learn. Giving the possibility to build more and more satisfactory knowledge.